2005
DOI: 10.1348/135532505x36778
|View full text |Cite
|
Sign up to set email alerts
|

An examination of the impact of community‐based rehabilitation on the offending behaviour of male domestic violence offenders and the characteristics associated with recidivism

Abstract: Purpose. The aim of this study was to examine the impact of completing a community‐based rehabilitation programme on both the rate of domestic violence reoffending, and time to first post‐treatment offence within an 11‐month follow‐up period. In addition, the pre‐treatment psychological, demographic, and offending history characteristics of recidivists were examined. Methods. Prior to attending West Midlands Probation Area's Domestic Violence Perpetrator Programme (DVPP), 86 male offenders completed a batter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 54 publications
2
37
0
3
Order By: Relevance
“…Przejawiają także więcej objawów niedostosowania emocjonalnego i wyższy poziom lęku od skazanych wewnątrzsterownych (Belniak, 2014). Nie stwierdzono natomiast różnic w tym zakresie pomiędzy recydywistami wielokrotnymi, a skazanymi po raz pierwszy (Bowen, Gilchrist, Beech, 2005). Ustalono także, że na obniżone poczucie sprawstwa wpływa doświadczanie sytuacji trudnych przed i w trakcie pobytu w zakładzie karnym.…”
Section: Poczucie Umiejscowienia Kontroli (Loc -Locus Of Control)unclassified
“…Przejawiają także więcej objawów niedostosowania emocjonalnego i wyższy poziom lęku od skazanych wewnątrzsterownych (Belniak, 2014). Nie stwierdzono natomiast różnic w tym zakresie pomiędzy recydywistami wielokrotnymi, a skazanymi po raz pierwszy (Bowen, Gilchrist, Beech, 2005). Ustalono także, że na obniżone poczucie sprawstwa wpływa doświadczanie sytuacji trudnych przed i w trakcie pobytu w zakładzie karnym.…”
Section: Poczucie Umiejscowienia Kontroli (Loc -Locus Of Control)unclassified
“…Despite the proliferation and expansion of intervention programs for batterers, different studies have produced variable and contradictory results. If, on one hand, some programs show positive results 26,27,32,33,35,37,39,43,47 , others do not reveal significant differences between the group that participated in the intervention and the group that did not receive intervention 20,28,42,52,54 . Some authors state that mixed results are due to either differences in terms of indicators and measures used in the assessment 17,22,66,65 or the success and efficacy definition 67 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, even though the majority of the studies stated the use of a quasi-experimental design, in fact the design was not a quasi-experimental one 26,29,30,[33][34][35]37,39,64 . This happens because among the identified studies were found: (i) studies without a control group 29,33,35,40 ; (ii) studies that assessed the effectiveness after the ending of the treatment (post-test design) 36,45,48 ; (iii) studies that used measures in the pre-and post-test (pre-post-test designs) 29,30,31,37,38,40 ; and (iv) studies with a non-equivalent control group 20,27,31 . Moreover, the programs without a control group did not provide a reference point in order to assess their effectiveness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Boira et al, 2013) different cohorts of men (e.g. Bowen et al, 2005) or different offender populations (e.g. Echauri et al, 2013).…”
Section: Experimental / Quasi-experimental Studiesmentioning
confidence: 99%